Estresse oxidativo em equinos submetidos à obstrução intraluminal do cólon menor - Bariani Junior, Antonio Fernando [UNESP] (2015)
The syndrome colic one of the most important disorders in horses, stand out among its causes obstructive frames, resulting from foreign bodies and or enteroliths located in the lower colon. The development of colic there is reduced local blood flow which follows, when their correction, blood reperfusion. The ischemia followed by reperfusion is the cause of increased postoperative primary degenerative injury. Reperfusion injury can be caused by the production and release of reactive oxygen species (ROS). In view of this, the aim of the present study to analyze molecules resulting from cellular oxidation and antioxidants in serum and lower colonic tissue in horses submitted to experimental intraluminal obstruction of the lower colon. They also evaluated physical parameters heart rate (HR), respiratory rate (RR), rectal temperature (Tr), motility, capillary refill time (TPC), color of mucous membranes, digital pulse and skin turgor. Hematological analysis and leukocytes were made at different times. Analysis of serum for determination of malondialdehyde (MDA) and vitamin E (Vit E), protein product of advanced oxidation (AOPP) (oxidation metabolites), glutathione (GSH) (antioxidant flux), were held at different times: M0 (time before the anesthetic and procedure obstruction), M4 (4 hours, removal of the obstruction), M12, M24, M36, M48, M60 and M72 (corresponding to 12, 24, 36, 48, 60 and 72 hours after occlusion). In the lower colon samples were obtained from M0 (before blocking) after 4 hours of intestinal obstruction (M4) were obtained in the oral region and aboral obstructed. After 72 hours of post surgical (M72) held new collection regions of the lower colon. In these tissue samples were carried out analysis of MDA, AOPP, catalase and GSH. In physiological parameters we observed a significant increase in HR and Tr in M12, and an increase in RR in M24. Hematological evaluation showed a decrease compared to red blood cell count ...